EVALUATION OF REASONS THE PROBLEMS DRILLINGS AND CASING IN DNIE-PER-DONETSK RIFT (Oil and Gas Engineering, 2017)
The article presents mainreasons of the drilling problems and well casing on the Dnieper-Donets rift (DDR). The dominant factors which is characterizingof well integrity study were showed. Inter-relation of geological, chemical and physical factors that have impact on the cementing quality were detected. Classification of defects cement sheath by genesis and influences quantityfor real isolation bore hole annulus were suggested. Mining-and-geological characteristics of well casing on the fields of the Dnieper-Donets rift were analyzed. The statistics of complication in the course of drilling in some wells of Dnieper-Donets rift for the 2000 - 2008 year were described. The article presentsdependence of well cement off control rheologic properties cementing slurry respectively reservoir conditions. Keywords: drilling problems, cement stone, well casing, wellbore leakage, Dnieper-Donets rift.